2022
DOI: 10.2196/33459
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Students About Plagiarism Using a Serious Game (Plagi-Warfare): Design and Evaluation Study

Abstract: Background Educational games have been proven to support the teaching of various concepts across disciplines. Plagiarism is a major problem among undergraduate and postgraduate students at universities. Objective In this paper, we propose a game called Plagi-Warfare that attempts to teach students about plagiarism. Methods To do this at a level that is beyond quizzes, we proposed a game storyline and mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Many researchers have discussed the user’s perception of a technology (Vazhayil and Shetty, 2019 ), and many have emphasized its legislative and regulatory issues (Khan et al, 2014 ). Therefore, careful selection is necessary to adopt or implement any technology (Ahmad and Shahid, 2015 ). Once imagined in films, AI now runs a significant portion of the technology, i.e., health, transport, space, and business.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have discussed the user’s perception of a technology (Vazhayil and Shetty, 2019 ), and many have emphasized its legislative and regulatory issues (Khan et al, 2014 ). Therefore, careful selection is necessary to adopt or implement any technology (Ahmad and Shahid, 2015 ). Once imagined in films, AI now runs a significant portion of the technology, i.e., health, transport, space, and business.…”
Section: Resultsmentioning
confidence: 99%
“…Innovation is very essential in addressing plagiarism. Approaches such as the “3-step approach” (Ng and Yip 2019 ), “Plagiarism warfare” (Ade-Ibijola et al 2022 ) and the “Goblin Threat” (Kier 2019 ) have been shown to improve awareness of plagiarism. However, the students in our study were reminded of the unacceptability of plagiarism when the assignment was given.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge gain [Aynsley et al, 2018] [Agbo et al, 2021] [Checa et al, 2021] [Ade-Ibijola et al, 2022] [Hsbollah & Rosli, 2022] [Hsbollah & Rosli, 2022] [Krishnan et al, 2023 Enjoyment [Aynsley et al, 2018] [Atmaja et al, 2020] [ Ade-Ibijola et al, 2022] [Krishnan et al, 2023 Educational development [Mercer et al, 2017] [Romero & Kalmpourtzis, 2020 Behavioral change [Mercer et al, 2017][ Ibrahim et al, 2018 Educational tool [Pettit et al, 2015] [Mercer et al, 2017] [Padilla-Zea et al, 2022] [Andrew Tong & Hee, 2023] Better learning outcomes [Nardo & Gaydos, 2021] [Rosa-Castillo et al, 2023 improvement [Pettit et al, 2015] [Pettit et al, 2015] [Hsbollah & Rosli, 2022] [Andrew Tong & Hee, 2023 Motivation improvement [Pettit et al, 2015] [Доброскок et al, 2020] [Frevert & Di Fuccia, 2021] [Agbo et al, 2021] [Wan et al, 2021] [Vodenicharova, 2022][Ade-Ibijola et al, 2022] [Zhyhadlo, 2022] [Andrew Tong & Hee, 2023 Learning effectiveness [Aynsley et al, 2018…”
Section: Benefit Examplesmentioning
confidence: 99%
“…Table 5 Challenges of educational game used in higher education. Challenge Study Lead-in [Mercer et al, 2017] [Checa et al, 2021 Expected outcomes [Ibrahim et al, 2018] [Nardo & Gaydos, 2021] Usability [Checa et al, 2021] [Ade-Ibijola et al, 2022] [Imam et al, 2022 Game design [Imam et al, 2022] [Soboleva et al, 2023 Teacher training [Доброскок et al, 2020][Hauge et al, 2021] [Kornevs et al, 2023 Constructive alignment [Mercer et al, 2017] [Romero & Kalmpourtzis, 2020 As shown in Table 4, 2 articles show that learners may need lead-in in gamify learning. Students who use games as an educational tool for the first time may not complete self-guide, they need supervisor or coach in course to support them or give them tutorials both in technology and psychology and adapt to the new learning tool.…”
Section: Benefit Examplesmentioning
confidence: 99%